2015
DOI: 10.4103/0019-5545.148516
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of eating disorder patients in India and Australia

Abstract: Background:Eating disorders (EDs) are an emerging concern in India. There are few studies comparing clinical samples in western and nonwestern settings.Aim:The aim was to compare females aged 16–26 years being treated for an ED in India (outpatients n = 30) and Australia (outpatients n = 30, inpatients n = 30).Materials and Methods:Samples were matched by age and body mass index, and had similar diagnostic profiles. Demographic information and history of eating and exercise problems were assessed. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Early diagnosis is the key to reduce the prevalence and complications of these illnesses [11]. There are very few studies concerning eating disorders and their associated risk factors among the Indian population [12][13][14]. Hence, in this study, we aim to estimate the prevalence of eating disorders and their associated risk factors such as stress, body mass index (BMI), body shape concerns, and other factors among students of various disciplines in a medical college hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis is the key to reduce the prevalence and complications of these illnesses [11]. There are very few studies concerning eating disorders and their associated risk factors among the Indian population [12][13][14]. Hence, in this study, we aim to estimate the prevalence of eating disorders and their associated risk factors such as stress, body mass index (BMI), body shape concerns, and other factors among students of various disciplines in a medical college hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Malhotra, Malhotra, and Pradhan (2014) have described two cases of adolescent girls who were diagnosed with anorexia in association with fear of fatness. These authors suggested that the clinical picture, risk factors, and response to treatment for anorexia in India “may be similar to that reported from the West” ( Malhotra et al., 2014 , p. 230; see also Lal et al., 2015 ). However, such claims are problematic in that they gloss over cases of food denial and extreme underweight as anorexia nervosa, as defined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; APA, 2013 ), while the broader context including gender, political economy, and social history remains unaddressed (S. Lee, 1995 , 1996 , 2001 , 2004 ).…”
mentioning
confidence: 76%
“…Given the significance of food and eating practices in India, there is surprisingly little scholarly literature on disordered eating. Most studies are case histories recorded by biomedical practitioners, particularly psychiatrists (but see Lal, Abraham, Parikh, & Chhibber, 2015 ; Srinivasan, Suresh, Jayaram, & Fernandez, 1995 ). For example, Chandra et al.…”
mentioning
confidence: 99%
“…[3] Perhaps, media-related glorification of “size zero” body type and culturally sanctioned drive for thinness, body shaming, and dissatisfaction have contributed to the recent upsurge of ED cases. [456] Traditionally, these parameters have been less of a concern in India than other countries. [4] Yet, another reason for the recent increase in the incidence of ED such as bulimia nervosa (BN) and binge eating disorder (BED) is more easy access to media outlets promoting unhealthy body types and higher socioeconomic status of people.…”
mentioning
confidence: 99%
“…[456] Traditionally, these parameters have been less of a concern in India than other countries. [4] Yet, another reason for the recent increase in the incidence of ED such as bulimia nervosa (BN) and binge eating disorder (BED) is more easy access to media outlets promoting unhealthy body types and higher socioeconomic status of people. [78]…”
mentioning
confidence: 99%